The proclivity of free-ranging indigenous village chickens for night-time roosting in trees - Takele Taye Desta (CABI Agriculture and Bioscience)
Abstract Background Roosting in trees exhibits the instinct and widespread practice of the night enclosure system in indigenous village chickens (IVCs) of the tropics. This work reviews the predisposition of IVCs for night-time roosting in trees and summarizes the pros and cons of this natural behavior. It is largely focused on personal insights which were then refined further by informal discussions. Besides, literature was consulted to recapitulate the accidental observational study. Main topics Night-time roosting in trees although in most instances is performed by a small proportion of farmers, is a widely practiced night enclosure system in the tropics. Roosting in trees eliminates the labor and the cost needed to construct night enclosures. It reduces contact with soiled bedding materials and droppings, parasites, and pathogens, consequently, it improves the health status and welfare of the family flock. It enables IVCs to express their inbuilt behavior and to evade predators. It carries the legacy of the ancient chicken rearing system and it is eco-friendly practice. However, in the absence of protective structures such as fences, it exposes IVCs to nocturnal predators and theft. However, this can be circumvented using guarding dogs. Birds might be also affected by adverse weather, although they are thought to be resilient to such environmental changes. Conclusions The sustainability, economic feasibility, and welfare of IVCs roosting in a tree need to be assessed to make it a justifiable practice. This piece of work likely elicits research questions to conduct an in-depth study on the existing systems of using trees as night-time roosting sites for IVCs.